Divorce under Coercion in the Maliki Jurisprudence Compared to the Jordanian and Kuwaiti Personal Status Law - Omar, Bassam Mohammad (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This research aims to clarify the Malikis’ rule on forced divorce, how they define the term "coercion," the evidence they used to come to their conclusion, the jurists (Fuqaha) who agreed with them, and those who disagreed with them. It also sought to identify aspects and ways not deemed coercion by Malikis by drawing parallels to the forced divorce provisions included in the personal status statutes of Jordan and Kuwait. The paper went on to detail actual cases heard by Sharia courts that involved coerced divorce. Methods: The comparative, the inductive, and the analytical method were used. The comparative method involved analyzing the various jurists ’ positions on divorce at the time of coercion. As part of the inductive method, a jurist’s opinions on divorce under coercion were examined. To gather evidence relevant to the current topic, the analytical method involved analyzing the texts of relevant jurists. Results: The Malikis believe that a forced divorce has no bearing, and that the wife is not then divorced. Divorce does not occur under Maliki law if one party has been forced to swear an oath under coercion or threatened with death or the death of one’s children. Blasphemy and defamation, conversely, are not considered coercion and can lead to a divorce. The findings also showed that Personal Status Law of Jordan and Kuwait does not recognize divorce under coercion, appealing to most jurists’ views. Conclusions: The forced divorce according to the Malikis does not take place and has no effect.